1988
DOI: 10.1039/ja9880300841
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the complete laser vaporisation of powdered solid samples into an inductively coupled plasma for atomic emission spectrometry

Abstract: The behaviour of solid materials on vaporisation by a continuous laser is described. The characteristics of the continuous-laser vaporisation have given rise t o a new concept of "complete laser vaporisation." A continuous-laser vaporisationinductively coupled plasma (ICP) system has been designed and tested for the direct analysis of powdered samples, consisting of a re-designed sample chamber and a continuous laser, rather than a pulsed laser, for the complete vaporisation of powdered samples. The sample vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The reason of the success of such a design, we believe, is to be attributed to the simplicity of construction (the machine workshop's task essentially limits to fixing a threaded cylinder on a slab), the flexibility for number of targets to be processed per measurement sessionthough neglecting issues of cross-contamination and flow dynamics -and also some lack of innovation drive on the side of the manufacturers. Unfortunately, after the appropriate optimizations reported by Arrowsmith and co-workers [17,19], the drum design represents a step back, considering the lack of attention for the gas flow dynamics, as also evident from the results of Su and Lin [21]. They designed and tested two types of closed-design ablation cells, i.e., a standard drum cell and again a bottle cell.…”
Section: Closed Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…The reason of the success of such a design, we believe, is to be attributed to the simplicity of construction (the machine workshop's task essentially limits to fixing a threaded cylinder on a slab), the flexibility for number of targets to be processed per measurement sessionthough neglecting issues of cross-contamination and flow dynamics -and also some lack of innovation drive on the side of the manufacturers. Unfortunately, after the appropriate optimizations reported by Arrowsmith and co-workers [17,19], the drum design represents a step back, considering the lack of attention for the gas flow dynamics, as also evident from the results of Su and Lin [21]. They designed and tested two types of closed-design ablation cells, i.e., a standard drum cell and again a bottle cell.…”
Section: Closed Cellsmentioning
confidence: 95%
“…Kantor [9] 1976 Designed for flame AAS Dittrich and Wennrich [14] 1980 Designed as closed system to avoid sample preparation (polishing) Thompson et al [13] 1981 Remote cell connected to the ICP via PVC tubing Carr and Horlick [11] 1982 Designed to fit ICP torch tail Ishizuka and Uwamino [12] 1982 Cap cell for polished surfaces (Aufsatz design) Gray [15] 2002 Cylindrical with tangential Ar inlet and adjustable sample height Arrowsmith [17] 1987 Bottle-shaped design with ablation direction parallel to gas flow Arrowsmith [19] 1988 Design with variable possible combination of gas flow inlet/outlet Mitchell et al [16] 1985 Designed for DCP spectrometry Su and Lin [21] 1986 Type I: standard cylindrical with symmetry axis normal to flow axis. Type II: bottle-shaped with tangential Ar introduction Gäckle and Güenther [7] 1988 Designed to fit into a petrographic microscope in the laser system Bleiner [23] 1990 Gun barrel: designed to minimize volume with many samples per run Piston cell: designed for flexible cell volume adjustment plume-shielding and possibly minimized molten droplet splashing, according to what was reported in Ref.…”
Section: Closed Cellsmentioning
confidence: 99%
“…In their experiments, an RSD value of 13% was obtained with pulsed ruby laser and an on-line deposition method by integrated absorbance measurement of lead in a solid sample. Su et al (25) were able to achieve statistically the same RSD (9%) in their CW laser ablation work for lead determination. A comparison of the experimental data for the two cells indicated that the effect of the gas flow pattern did not play a major role in the analytical performance of the system.…”
Section: Analytical Performancementioning
confidence: 81%
“…For many solids, a power density in the range from 10 4 to 10 9 W cm 02 is required for evaporation (24). A continuous wave laser vaporization system was demonstrated by Su et al (25). In their work, a 50 W CW YAG laser was used at 1064 nm.…”
Section: Introductionmentioning
confidence: 99%
“…With laminar flow in the chamber, entrainment efficiency and thus detection characteristics are improved; turbulent flow contributes to losses by trapping particles in stagnant flow regions. 46 The volume of the chamber is an important parameter; a larger internal volume can lead to sample dilution and memory effects. Because LA processes are transient in nature, larger chamber volumes may be advantageous for signal averaging during repetitive sampling experiments.…”
Section: Ablation Chamber and Transport Tubingmentioning
confidence: 99%